System for art and identity in Mesoamerica and the Caribbean (SAVIA) of the ICAT program - Gerner, Vera (2016)
In its research projects, the Program for Cultural Identity, Art and Technology (ICAT) always has worked closely with artists, communities, public and private institutions and national and international organizations. In these processes, we observed that the diverse entities and actors approach art in very different ways, generating proposals for creative exploration and research that are different, but at the same time-share issues and develop complementary methodologies. Despite this compatibility, there is little exchange beyond the borders of specific professions or fields of study, and spaces as forums, social networks and calls for papers or projects, that are crated in order to promote the exchange, tend to segregate art in categories that make it difficult to think beyond these bordures. It was because of this concern that the ICAT program decided to create the SAVIA project. SAVIA is a platform that seeks to encourage the exchange of materials, experiences and initiatives concerning the exploration, documentation and research of art and regional cultural identity, transcending the boundaries of specific occupations or fields of study. This encouragement is made through the development of shared documentation projects, an on-line platform, a system for the management of audiovisual material and activities aimed at creating a network of mutual support.